Thermal degradation and mechanical behavior of banana pseudo-stem reinforced composites - Hassan, Mohamad Zaki; Salit, Mohd Sapuan; A. Rasid, Zainudin (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Banana fiber has potential to beutilized in bio-based composite structures due to its low price, abundantly available and biodegradability. However, the performance of this fiber is still not comparable tothe synthetic polymeric system. In this work, the thermal stabilityanalysisand tensile test of optimized banana fiber thatwasinitially evaluated using response surface method wereconducted. The thermal analysisand the tensile testwere conducted using thermogravimetric analyzer and universal testing machinerespectively. It was shown that thebanana fiber content offered an outstanding performance in thermal stability. The highest thermal stability however,was found in neat epoxy resin system. The TG and DTG resultsshowedthe lowest amount of residueoccurredin banana/epoxy composite. The tensile data propertiesrevealed that banana compositeis comparable tosynthetic samples.